Development of pineapple harvesting attachment for brush cutter - ATHIRA PRASAD SHAHAMA K MUKESH KUMAR; Shivaji K.P (Guide) (Tavanur 2016 DEPARTMENT OF FARM POWER MACHINERY AND ENERGY)
Development of pineapple harvesting attachment for brush cutter
Development of pineapple harvesting attachment for brush cutter